Pragmatic Human-Centred Design in Action: Assessing the Tone and Usability of the Behaviours in Dementia Toolkit Website - Ubels, Nick; Albrecht, Lauren; Koh, Woon Chee; Conn, David (Evidence Based Library and Information Practice, 2026)
Objective – The Behaviours in Dementia Toolkit is an online library to support dementia-related mood and behaviour changes. It is intended to be used by two key caregiving audiences: 1) formal, professional care partners, and 2) informal care partners. The purpose of this study was to assess the content tone and usability of the website to meet the needs of its two user groups.Methods – The multi-method design included electronic surveys and interviews. Content tone was assessed using word reaction and highlighter tests. Task-specific usability was assessed with the single-ease question (SEQ), time on task, and completion rate. The System Usability Scale (SUS) measured overall usability before and after design changes based on initial results.Results – Content tone was friendly, trustworthy, desirable, and clear, but informal care partners found medical jargon confusing. Task-specific usability was generally acceptable. Time one SUS score for formal care partners was assessed at a letter grade A, but for informal care partners was a C. Content tone and usability testing drove critical changes to the library. Time two SUS scores subsequently equalized for the user groups to an A- for formal care partners and a B for informal care partners. Divergent requirements for formal and informal care partners were identified and addressed using pragmatic human-centred design methods.Conclusion – Jargon, information overload, and search flow require careful attention in an online health information library. Digital libraries and other projects facilitating access to health information seeking groups may find these usability methods useful to consider at the outset of their project planning given the actionable insights they can provide. These techniques are suitable for projects with a limited budget and tight timeframe.